The impact of occupational health and safety system implementation on work-related illnesses among drilling rig workers: A review article - Heri Wardana; Rozi Mexiwel; Achmad Jusuf Zulfikar (TEKNOSAINS : Jurnal Sains, Teknologi dan Informatika, 2025)
The oil and gas drilling industry is widely recognized as a high-risk sector in terms of occupational safety and health (OSH). Workers in this field are frequently exposed to a range of physical, chemical, biological, and ergonomic hazards, which significantly increase their vulnerability to various occupational diseases (ODs). These include, but are not limited to, respiratory disorders, musculoskeletal injuries, and dermatological conditions. Given the complex and hazardous nature of drilling operations, implementation a comprehensive and systematic OSH management system has become essential. This review article aims to synthesize recent literature examining the relationship between the application of Occupational Safety and Health (OSH) systems and the prevention of occupational diseases among drilling rig workers. A thorough evaluation of both national and international studies published in the last five years reveals that effective implementation plays a critical role in reducing the incidence of ODs. The findings consistently highlight that the most significant improvements are achieved through proactive risk control measures, ongoing worker training programs, and continuous environmental monitoring. These strategies, when integrated into daily operations, contribute to creating a safer work environment, thereby enhancing both worker well-being and overall operational efficiency in high-risk industries such as oil and gas drilling.